Corn Starch/Soybean Wax Double Coated Biochar‑based Controlled‑release Nitrogen Fertilizer: Water Retention, Release Kinetics and Okra Growth - Isobel Joo Xing, Yong; Ivy Ai Wei, Tan; Daniel Hong Heng, Sim; Leonard Lik Pueh, Lim (Springer Nature, 2026)
Water-soluble fertilizers, although widely used to enhance crop productivity, often lead to environmental pollution due to their rapid nutrient loss. To address this issue, coated biochar-based fertilizers have gained attention for improving nutrient use efficiency and reducing environmental impacts, with their performance greatly depends on the formulation of the encapsulating materials. Biopolymers such as starch offer a biodegradable alternative to synthetic polymers, while soybean wax provides an environmentally-friendly and highly hydrophobic coating capable of enhancing the controlled-release behaviour. Together, these materials present a promising strategy for developing more sustainable controlled-release fertilizer formulations. In this study, a double-layered coated biochar-based fertilizer was synthesized using corn starch as the inner coating and soybean wax as the outer layer to enhance the nutrient release performance and support sustainable agriculture. The double-coated formulation improved the water retention and slowed the nitrogen release as compared with the uncoated fertilizer, following a zero-order kinetic mechanism. These controlled-release characteristics enhanced the plant performance as evidenced by the increased okra height. Overall, the corn starch/soybean wax coating demonstrated a strong potential for reducing the nutrient loss while promoting crop growth.